Therapeutic Potential of the Hsp90/Cdc37 Interaction in Neurodegenerative Diseases - Gracia, Liam; Lora, Gabriella; Blair, Laura J.; Jinwal, Umesh K. (Frontiers in Neuroscience, 2019)
Alzheimer’s, Huntington’s, and Parkinson’s are devastating neurodegenerative diseases that are prevalent in the aging population. Patient care costs continue to rise each year, because there is currently no cure or disease modifying treatments for these diseases. Numerous efforts have been made to understand the molecular interactions governing the disease development. These efforts have revealed that the phosphorylation of proteins by kinases may play a critical role in the aggregation of disease-associated proteins, which is thought to contribute to neurodegeneration. Interestingly, a molecular chaperone complex consisting of the 90kDa heat shock protein (Hsp90) and Cell Division Cycle 37 (Cdc37) has been shown to regulate the maturation of many of these kinases as well as regulate some disease-associated proteins directly. Thus, the Hsp90/Cdc37 complex may represent a potential drug target for regulating proteins linked to neurodegenerative diseases, through both direct and indirect interactions. Herein, we discuss the broad understanding of many Hsp90/Cdc37 pathways and how this protein complex may be a useful target to regulate the progression of neurodegenerative disease.